Overcoming Technological Barriers to Instruction: Situating Gen Z Students as Reverse Mentors - Frey, T. Kody (Frontiers in Communication, 2021)
In response to a changing higher education landscape, this essay presents an argument for utilizing reverse mentoring to solve technological problems in the academy. Specifically, the essay argues that a) Gen Z students are uniquely positioned to capitalize on reverse mentoring programs and b) instructional communication is an important framework for future reverse mentoring research.